2017
DOI: 10.1111/gcb.13845
|View full text |Cite
|
Sign up to set email alerts
|

Variable silicon accumulation in plants affects terrestrial carbon cycling by controlling lignin synthesis

Abstract: Current climate and land-use changes affect regional and global cycles of silicon (Si), with yet uncertain consequences for ecosystems. The key role of Si in marine ecology by controlling algae growth is well recognized but research on terrestrial ecosystems neglected Si since not considered an essential plant nutrient. However, grasses and various other plants accumulate large amounts of Si, and recently it has been hypothesized that incorporation of Si as a structural plant component may substitute for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 41 publications
(64 reference statements)
9
67
1
Order By: Relevance
“…For references of the wave numbers for the different compounds see Table 1. This relative decrease in contribution of carbohydrates is not necessarily in contradiction with the reported reduction of absolute carbohydrate concentration due to increased Si content (Schoelynck et al 2010;Schaller et al 2012a;Klotzbücher et al 2018). It was already suggested that Si accumulation leads to a decrease in cellulose, lignin and phenol concentrations in plants (Schoelynck et al 2010;Schaller et al 2012a;Klotzbücher et al 2018).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…For references of the wave numbers for the different compounds see Table 1. This relative decrease in contribution of carbohydrates is not necessarily in contradiction with the reported reduction of absolute carbohydrate concentration due to increased Si content (Schoelynck et al 2010;Schaller et al 2012a;Klotzbücher et al 2018). It was already suggested that Si accumulation leads to a decrease in cellulose, lignin and phenol concentrations in plants (Schoelynck et al 2010;Schaller et al 2012a;Klotzbücher et al 2018).…”
Section: Discussionmentioning
confidence: 54%
“…It was shown that Si content is negatively related to carbon contents in aboveground biomass of plants (Neu et al 2017;Klotzbücher et al 2018). It was also found that Si content affects the carbon quality of aboveground plant biomass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, several studies have found negative correlations between silicon and total carbon, phenolics and lignin, indicating a consistent carbon–silicon trade‐off in plants (Frew, Powell, Sallam, Allsopp, & Johnson, 2016; Klotzbücher et al, 2018). The proposed mechanism for this trade‐off is that grasses can use Si as a substitute for more energetically costly carbon‐based compounds (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Hashemi, Abdolzadeh, and Sadeghipour () showed that Si prevents an increased cell wall lignification in plants under salinity stress. In addition, there is evidence for a trade‐off between carbon‐based compounds and Si‐based defences in some Si‐accumulator plants, in which Si‐treated plants may exhibit reduced carbon compounds (Cooke & Leishman, ; Frew, Powell, Sallam, Allsopp, & Johnson, ; Klotzbücher et al, ; Schaller, Brackhage, & Dudel, ). However, in relation to lignin, hemicellulose and cellulose contents, collard was not influenced by Si fertilization under different conditions of soil moisture.…”
Section: Discussionmentioning
confidence: 99%